Examining the Role of Self-Discrepancy and Self-Directed Style in Bulimia Nervosa - Mason, Tyler B. (Psychiatry Res, 2016)
Two of the primary components within Integrative Cognitive Affective Therapy (ICAT) are self-discrepancy and self-directed style. Self-discrepancy includes both actual:ideal (discrepancy between oneself and who one wishes they were) and actual:ought (discrepancy between oneself and who one believes they ought to be). Self-directed style in ICAT refers to a variety of behaviors emitted by a person toward the self including self-blaming and self-affirming. This study explored main effects and interactions between self-discrepancy and self-directed style in relation to global eating disorder (ED) psychopathology, depressive symptoms, and anxiety. Eighty treatment-seeking adults from the Midwest with BN or subthreshold BN completed interviews and self-report measures. Self-affirm and self-blame were associated with ED psychopathology, depressive symptoms, and anxiety. Actual:ideal discrepancy was related to anxiety and actual:ought discrepancy was related to anxiety and depression. Interactions were found between self-affirm and actual:ought discrepancy as well as self-blame and actual:ought discrepancy and depressive symptoms. High actual:ought was related to increased depressive symptoms regardless of levels of self-affirm and self-blame. Effect sizes for models were medium-to-large with anxiety models demonstrating the largest effects. This study provides further evidence supporting the ICAT model and treatment, which targets self-discrepancies, self-directed styles, and related emotional states.